POLAR-guided signalling complex assembly and localization drive asymmetric cell division - Houbaert, Anaxi (2018)
Stomatal cell lineage is an archetypal example of asymmetric cell division (ACD), which is necessary for plant survival1–4. In Arabidopsis thaliana, the GLYCOGEN SYNTHASE KINASE3 (GSK3)/SHAGGY-like kinase BRASSINOSTEROID INSENSITIVE 2 (BIN2) phosphorylates both the mitogen-activated protein kinase (MAPK) signalling module5,6 and its downstream target, the transcription factor SPEECHLESS (SPCH)7, to promote and restrict ACDs, respectively, in the same stomatal lineage cell. However, the mechanisms that balance these mutually exclusive activities remain unclear. Here we identify the plant-specific protein POLAR as a stomatal lineage scaffold for a subset of GSK3-like kinases that confines them to the cytosol and subsequently transiently polarizes them within the cell, together with BREAKING OF ASYMMETRY IN THE STOMATAL LINEAGE (BASL), before ACD. As a result, MAPK signalling is attenuated, enabling SPCH to drive ACD in the nucleus. Moreover, POLAR turnover requires phosphorylation on specific residues, mediated by GSK3. Our study reveals a mechanism by which the scaffolding protein POLAR ensures GSK3 substrate specificity, and could serve as a paradigm for understanding regulation of GSK3 in plants.